Renaissance Cultural Crossroads - University of Warwick - Centre for the Study of the Renaissance (2010)
"The Renaissance Cultural Crossroads Catalogue is a searchable, analytical and annotated list of all translations out of and into all languages printed in England, Scotland, and Ireland before 1641. It also includes all translations out of all languages into English printed abroad before 1641." [self-description]